2015
DOI: 10.1002/cphc.201500907
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Plasmonic Cu2‐xSe@ZnS Core@Shell Nanoparticles

Abstract: We report the synthesis of plasmonic Cu2-x Se@ZnS core@shell nanoparticles (NPs). We used a shell growth approach, starting from Cu2-x Se NPs that have been shown before to exhibit a localized surface plasmon resonance (LSPR). By careful synthesis planning we avoided cation exchange reactions and received core@shell nanoparticles that, after oxidation under air, exhibit a strong LSPR in the NIR. Interestingly, the crystalline, closed ZnS shell that we grew with variable thickness still allowed a slow oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…The increase of the (NH 4 ) 2 MoS 4 concentration leads to the dissolution of Cu 2−x S particles and the reformation of amorphous Cu 2 MoS 4 . [178] In a recent work by Wolf et al [180] the LSPR in copper selenide NCs was stabilized by growing a ZnS shell around them. Indeed, it was observed that the oxidation of the copper chalcogenide core under ambient conditions is slowed down dramatically compared to the bare Cu 2-x Se NCs.…”
Section: Copper Chalcogenide (Cu 2−x E; E=s Se and Te) Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of the (NH 4 ) 2 MoS 4 concentration leads to the dissolution of Cu 2−x S particles and the reformation of amorphous Cu 2 MoS 4 . [178] In a recent work by Wolf et al [180] the LSPR in copper selenide NCs was stabilized by growing a ZnS shell around them. Indeed, it was observed that the oxidation of the copper chalcogenide core under ambient conditions is slowed down dramatically compared to the bare Cu 2-x Se NCs.…”
Section: Copper Chalcogenide (Cu 2−x E; E=s Se and Te) Ncsmentioning
confidence: 99%
“…Indeed, it was observed that the oxidation of the copper chalcogenide core under ambient conditions is slowed down dramatically compared to the bare Cu 2-x Se NCs. Instead, the core was effectively protected from reduction, even in the presence of reducing agents such as borane tert-butyamine complex and diisobutylaluminum hydride, giving rise to a stable particle LSPR, also under strongly reducing conditions [180].…”
mentioning
confidence: 99%
“…Combination of metal NPs with vacancy‐doped plasmonic semiconductor nanocrystals together will open the access to unexplored phenomena resulting from the coupling between the collective electronic oscillation at surface of metal NPs and the hole oscillation in the neighboring semiconductors . Many metal‐semiconductor hetero‐nanostructures have been synthesized and the plasmonic properties have been investigated . Jiang et al.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 13 , 16 18 This makes Cu 2– x A NCs promising materials for photovoltaics, 15 photocatalysis, 19 sensing, 20 and nanoplasmonics. 9 , 11 , 17 , 21 , 22 …”
Section: Introductionmentioning
confidence: 99%